Conversion of steel by polyphenolic model molecules: Corrosion inhibition mechanism by rutin, esculin, esculetol. (15th May 2018) - Veys-Renaux, Delphine; Reguer, Solenn; Bellot-Gurlet, Ludovic; Mirambet, François; Rocca, Emmanuel
Graphical abstract: Highlights: Radical scavenging properties of antioxidant molecules induce cathodic inhibition. Free-catechol molecules form an octahedral tri-catecholate complex with iron (III). The growth of a conversion film of catecholate complex provides an anodic inhibition. Glycosylated catechol molecules are rather adsorbed on oxidized iron film. Abstract: This paper focuses on the potential corrosion protection of steel in presence of three polyphenolic model molecules (rutin, esculin, esculetol) in a weak acidic medium (pH = 4). From an electrochemical point of view, the cathodic inhibition was attributed to the oxygen scavenger role of the considered antioxidant compounds. SEM observations, Raman spectroscopy and Synchrotron X-ray absorption spectroscopy revealed furthermore the formation of a surface film by precipitation of iron polyphenolate conversion products, in which iron III is likely coordinated with free-catechol groups. Glycosylated catechol groups are rather adsorbed on a FeOOH layer.